STUDENT RESPONSES TO THE ONLINE LEARNING PROCESS FOR CAPITA SELECTA EDUCATION MANAGEMENT COURSES - Muhammad Yasir Arafah; Sedya Santosa; Heldy Ramadhan Putra (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
This research focuses on the Kapita Selecta Education Management course which is conducted online. The aim of this research is to find out student responses before and after attending online lectures, especially related to the effectiveness and efficiency of online courses and student responsibilities in doing assignments online. The implementation of this online activity was only carried out for 4x meetings and 12x meetings were conducted face-to-face. This research uses quantitative methods. Data collection techniques were carried out through a google form questionnaire and continued with quantitative descriptive data analysis. The result is that online learning is quite effective and efficient to replace face-to-face lectures. Online learning increases enthusiasm and responsibility in doing assignments on time in the Kapita Selecta Education Management course. Online learning can be used as an alternative to overcome the problem of effective and efficient meetings between lecturers and students.